Electronic structure and flotation behavior of monoclinic and hexagonal pyrrhotite - Zhao, Cui-hua; Wu, Bo-zeng; Chen, Jian-hua (Journal of Central South University, 2015)
Electronic structures of monoclinic and hexagonal pyrrhotite were studied using density functional theory method, together with their flotation behavior. The main contribution of monoclinic pyrrhotite is mainly from Fe 3d, while that of hexagonal pyrrhotite is from Fe 3d, Fe 3p and S 3s. The hexagonal pyrrhotite is more reactive than monoclinic pyrrhotite because of large density of states near the Fermi level. The hexagonal pyrrhotite shows antiferromagnetism. S—Fe bonds mainly exist in monoclinic pyrrhotite as the covalent bonds, while hexagonal pyrrhotite has no covalency. The main contributions of higest occupied molecular orbital (HOMO) and lowest unoccupied molecular obital (LUMO) for monoclinic pyrrhotite come from S and Fe. The main contribution of HOMO for hexagonal pyrrhotite comes from Fe, while that of LUMO comes from S. The coefficient of Fe atom is much larger than that of S atom of HOMO for hexagonal pyrrhotite, which contributes to the adsorption of CaOH + on the surface of hexagonal pyrrhotite when there is lime. As a result, lime has the inhibitory effect on the floatation of hexagonal pyrrhotite and the coefficient of Fe is very close to that of S for monoclinic pyrrhotite. Therefore, the existence of S prevents the adsorption of CaOH + on the surface of monoclinic pyrrhotite, which leads to less inhibitory effect on the flotation of monoclinic pyrrhotite.